A dimensional framework for the use of ASPD in SVP civil commitment. Issue 1 (2nd January 2021) - Rokop, James; DiCiro, Melinda; Sreenivasan, Shoba; Weinberger, Linda E.
ABSTRACT: The U.S. Supreme Court indicated in Kansas v. Crane that a qualifying mental disorder for Sexually Violent Predator civil commitment must differentiate between the 'dangerous sexual offender' and the 'ordinary criminal recidivist, ' an issue of particular relevance when Antisocial Personality Disorder is the diagnosed condition. The DSM-5 categorical framework can be problematic in forensic contexts where the legal definition calls for a complex, layered, and nuanced approach. Dimensional schemes describe personality pathology in a flexible, individualized, and in-depth manner. In this paper we propose the expansion of DSM-5 ASPD criteria through the Alternative Model for Personality Disorders as a dimensional bridge to the SVP legal definition of a mental disorder. To that end, we first explain why a dimensional framework is plausible for the SVP definition of a mental disorder. Next, we review dimensional elements of ASPD impairments that serve to differentiate the sexually dangerous person from the ordinary criminal recidivist. Lastly, we provide a practical model that a forensic evaluator can use to determine whether to accept or reject ASPD as a viable SVP mental disorder.